2017
DOI: 10.3329/jssmc.v6i2.31768
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Fibrocalcous Pancreatic Diabetes (FCPD) In Children and Adolescents in a Tertiary Hospital

Abstract: Background: Fibrocalculous pancreatic diabetes (FCPD) is a unique form of diabetes secondary to nonalcoholic, chronic, calcific, pancreatitis seen in tropical, developing countries of the world.Objective: The purpose of the present study was to determine the clinical features & the glycemic status of the children and adolescents with FCPD. Methodology: This descriptive study was undertaken in the department of paediatrics and at the data retrieval centre of Bangladesh Institute of Research and Rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…10 There is a marked male preponderance, but in a Bangladeshi study revealed that 81% of their FCPD patient were girl and 68% were from rural areas like our case. 11 The investigation of choice for the diagnosis is a plain X-ray of the abdomen, which will reveal the presence of the characteristic pancreatic calculi crossing the midline at the level of calculi are mostly situated to the right of the first or second lumbar vertebrae, but may rarely overlap the spine which are usually large in size and extend throughout the pancreas. Ultrasound examination of the abdomen is also useful and will pick up pancreatic duct dilatation in addition to calcification and calculi.…”
Section: Diagnostic Criteria For Fcpdmentioning
confidence: 99%
“…10 There is a marked male preponderance, but in a Bangladeshi study revealed that 81% of their FCPD patient were girl and 68% were from rural areas like our case. 11 The investigation of choice for the diagnosis is a plain X-ray of the abdomen, which will reveal the presence of the characteristic pancreatic calculi crossing the midline at the level of calculi are mostly situated to the right of the first or second lumbar vertebrae, but may rarely overlap the spine which are usually large in size and extend throughout the pancreas. Ultrasound examination of the abdomen is also useful and will pick up pancreatic duct dilatation in addition to calcification and calculi.…”
Section: Diagnostic Criteria For Fcpdmentioning
confidence: 99%